MENDIDIK INSAN BERILMU YANG BERHATI TEDUH, BERPIKIR SOLUTIF DAN BERTINDAK ETIS: MENCARI SEBUAH HUMANISME INTEGRAL DI TENGAH KRISIS ANTROPOLOGIS - Sutam, Inosensius (Jurnal Pendidikan dan Kebudayaan Missio, 2016)
Abstract: To Educate a Human  Having Science, Calm Heart, Solutive Thought, and Ethical Action: To Search an Integral Humanism in the Midst of an Antrhopological Crisis. To educate is the whole efforts of transforming someone, that he/she becomes a qualified human being, or human of a golden heart.  The golden human is a scientific person, having a calm heart, having a solutive thought, and ethical action. Having a science, or to possess a science is very important to support human existence.  Here, we often face with agitation between to have and to be.  Therefore, we need harmony in three centres of power within human’s self, namely heart, thought, and action.  A calm heart becomes the source of beauty (beautiful-ugly), and spirituality (sanctity-wicked). The thought becomes the source for rationality (right-wrong), that can give way out toward all problems that are faced by  human. The contents of heart and mind are expressed in action. Human’s activity (actus humanus) is sourced on ethics (good–evil).  Humans with a calm heart, solutive mind, ethical action, will be the integral human, and that matter will yield/result an integral humanism, namely the holistic notion/understanding on human, where all one’s life facets/aspects get the same and equal attention.Keywords: to educate, having a calm heart, having a solutive thought, having ethical action, integral humanism Abstrak: Mendidik insan berilmu yang berhati teduh, berpikir solutif dan bertindak etis:  mencari sebuah humanisme integral di tengah krisis antropologis. Mendidik adalah seluruh upaya untuk mentransformasikan seseorang, sehingga ia menjadi manusia bermutu atau manusia (berhati) emas. Manusia emas adalah orang yang berilmu, berhati teduh, berpikir solutif dan bertindak etis. Berilmu atau memiliki ilmu  sangat penting untuk mendukung keberadaan manusia. Di sini sering kita berhadapan dengan ketegangan antara memiliki dan ada. Karena itu  kita membutuhkan keharmonisan dalam tiga  pusat kekuatan dalam diri manusia, yaitu hati, pikiran, dan tindakan. Hati yang teduh menjadi sumber keindahan (indah-jelek) dan spiritualitas (suci-jahat). Pikiran menjadi sumber rasionalitas (benar-salah), yang dapat memberi jalan keluar terhadap semua masalah yang dihadapi manusia. Isi hati dan pikiran diungkapkan dalam tindakan. Tindakan manusiawi (actus humanus) bersumberkan etika (baik-buruk).  Manusia yang  mempunyai hati teduh, pikiran solutif, dantindakan etis akan menjadi manusia integral, dan hal itu akan menghasilkan sebuah humanisme integral, yaitu pemahaman yang menyeluruh tentang manusia, di mana semua aspek kehidupannya   mendapat perhatian yang sama dan seimbang. Kata kunci: berhati teduh, berpikir solutif, bertindak etis, humanisme integral